2021
DOI: 10.3390/nu13051613
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of the Branched-Chain Amino Acids, Leucine, Isoleucine and Valine, on Gastric Emptying, Plasma Glucose, C-Peptide and Glucagon in Healthy Men

Abstract: (1) Background: Whey protein lowers postprandial blood glucose in health and type 2 diabetes, by stimulating insulin and incretin hormone secretion and slowing gastric emptying. The branched-chain amino acids, leucine, isoleucine and valine, abundant in whey, may mediate the glucoregulatory effects of whey. We investigated the comparative effects of intragastric administration of leucine, isoleucine and valine on the plasma glucose, C-peptide and glucagon responses to and gastric emptying of a mixed-nutrient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In the current study, HI improved the glucose clearance after the meal test. This was in line with previous studies showing that intragastric infusion of Ile and Leu in healthy males [ 76 , 77 ] or oral administration of Ile in rats [ 78 , 79 , 80 ] and healthy humans [ 81 ], but not Val, decreased the postprandial blood glucose. This is while intravenous infusion of Val in healthy humans [ 82 ] or its oral administration in rats [ 79 ] either marginally decreased or raised blood glucose concentration, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, HI improved the glucose clearance after the meal test. This was in line with previous studies showing that intragastric infusion of Ile and Leu in healthy males [ 76 , 77 ] or oral administration of Ile in rats [ 78 , 79 , 80 ] and healthy humans [ 81 ], but not Val, decreased the postprandial blood glucose. This is while intravenous infusion of Val in healthy humans [ 82 ] or its oral administration in rats [ 79 ] either marginally decreased or raised blood glucose concentration, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…However, a factor which has to be taken into consideration is that amino acids produce a slowing down of stomach emptying that could explain, in part, the observed metabolic responses. Certainly, intragastric administration of L-leu and L-ile in healthy men lowers postprandial blood glucose, at least in part by slowing gastric emptying [ 47 ]. Additionally, studies in Sprague-Dawley rats have shown that L-arg and other amino acids inhibit and delay gastric emptying as evaluated by a breath test using [1- 13 C] acetic acid [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that the changes in isoleucine level in patients with GDM may be caused by changes in P-gp, ABCC8, and ABCC9 expression. Numerous studies (Doi et al, 2005;Doi et al, 2007;Ikehara et al, 2008;Guasch-Ferréet al, 2016;Ullrich et al, 2016;Newmire et al, 2019;Elovaris et al, 2021a;Elovaris et al, 2021b) have suggested that the effect of isoleucine on glucose metabolism may be related to the decreased expression of glucose-6-phosphatase (G6Pase). In the present study, we found that glucose 6-phosphate (G6P) level was elevated after pregnancy, presumably due to a decrease in G6Pase expression.…”
Section: Discussionmentioning
confidence: 99%